Evaluasi Kesuksesan Implementasi Sasaran Kinerja Pegawai (SKP) di Kabupaten Sidoarjo berdasarkan Model DeLone and McLean - Alfian Fannani; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sidoarjo government has implemented e-government for employees named Sasaran Kinerja Pegawai (SKP) to provide services for employees in work performance assessments. However, in daily use SKP still has a various of problems. This study aims to describe variable in the DeLone and McLean model to find out the success of SKP in Sidoarjo. The DeLone and McLean model consists of variables of information quality, system quality, service quality, intention to use, user satisfaction, and net benefits. Descriptive statistical approach ware applied to processed data from 120 employees of e-government system by distributing 10 questionnaires to 12 Satuan Kerja Pangkat Daerah (SKPD) in Sidoarjo. The finding of this study that the success rate of SKP in Sidoarjo from the perspective of employees with a percentage of 82.34% was included in the 'Very High' category. However, there are still three variables that have values below the average, namely the variable information quality with the lowest indicators of relevance, accuracy, and completeness; system quality with the lowest indicators of integration; and service quality with the lowest indicators of responsive and empathy. As a recommendation, the variable that is still below the average needs to be optimized through improvement.